Versuche mit FFS "Solea" zum Fang von Tiefseegarnelen (Pandalus sp.) im September 1984 - Mohr, H.; Horn, W. (1984)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010